IMPLEMENTASI KOMPONEN KEGIATAN PENGENDALIAN SISTEM PENGENDALIAN INTERN PEMERINTAHAN (SPIP) DALAM MEWUJUDKAN PRINSIP TRANSPARANSI PADA DISBUDPAR ACEH - Iradah, Nirma Via; Yahya, Muhammad Rizal (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
This study aims to determine the implementation of control activities of Government Internal Control System at Disbudpar Aceh by looking at the elements of control activities, namely reviewing the performance of the relevant agencies, fostering human resources, controlling over managing information systems, physical control over assets, determining and reviewing on performance indicators and measures, segregation of functions, authorization of important transactions and events, accurate and timely recording of transactions and events, restrictions on access to resources and their records, accountability of resources and their recording, good documentation of internal control systems and important transactions and events that instill transparency. This research is a case study research with a descriptive-qualitative paradigm approach and interviews as a method of collecting data. The results of this study show that Disbudpar Aceh has implemented the eleven elements of control activities of Government Internal Control System in accordance with PP No. 60/2008, in which the application of control activities made a good contribution to the Disbudpar Aceh in creating the transparency